Upaya Meningkatkan Minat Belajar Siswa pada Mata Pelajaran Ilmu Pengetahuan Alam (IPA) Menggunakan Metode Kooperatif Tipe Team Games Tournament (TGT) di Kelas III SD GMIT Nenu - Yulius Amtiran (Edukasi Elita : Jurnal Inovasi Pendidikan, 2025)
Learning interest is one of the key factors influencing students' success in understanding a subject. In reality, many students struggle to engage with Natural Science (IPA) lessons due to less interactive and conventional teaching methods. The Team Games Tournament (TGT) cooperative learning model is an approach that can be used to enhance students' interest in learning through engaging games and academic competitions.This study aims to increase the learning interest of third-grade students at SD GMIT Nenu in Natural Science (IPA) by implementing the TGT method. The research employs a Classroom Action Research (CAR) method, conducted in two cycles, each consisting of planning, implementation, observation, and reflection. The research subjects were 16 third-grade students at SD GMIT Nenu in the 2022/2023 academic year. Data collection techniques included observations, learning interest questionnaires, interviews, and learning outcome tests. The collected data were analyzed using qualitative and quantitative descriptive techniques.The results indicate that the implementation of the TGT method significantly increased students' learning interest. Before the intervention, only 45% of students demonstrated a high interest in learning, with an average test score of 65.0. After applying the TGT method in the first cycle, learning interest increased to 75%, and the average student score improved to 80.5. In the second cycle, students' learning interest reached 93.75%, with an average score rising to 98.12. These findings demonstrate that the TGT method makes learning more engaging, fosters student interaction, and helps them understand scientific concepts more effectively.Based on these findings, it can be concluded that the TGT cooperative learning method is effective in enhancing elementary school students' learning interest. Teachers are encouraged to adopt this method for teaching Natural Science or other subjects that require active student participation. Furthermore, future research can be conducted to explore the effectiveness of this method in higher education levels and in different classroom settings.